Impact of Dentures on Oral Health-Related Quality of Life in Community-Dwelling Older Adults in Yogyakarta - Astuti, Novitasari Ratna; Cinthara, Yuananda Trie (Proceedings International Conference on Sustainable Innovation (ICoSI), 2025)
Tooth loss is a major concern as it can lead to masticatory dysfunction, speech impairment, and aesthetic issues. The use of dentures is crucial for older adults with tooth loss, significantly affecting their oral health-related quality of life (OHRQoL). The purpose of the study was to investigate the impact of dentures on the OHRQoL elderly community living in Yogyakarta. Seventy elderly patients who had treatment at PKU Muhammadiyah and Aisyiyah clinics in Yogyakarta for complete dentures (CD) and removable partial dentures (RPD) participated in this cross-sectional descriptive study. Oral health impact was evaluated using the Oral Health Influence Profile (OHIP) questionnaire. Denture types and usage, as well as demographics, were included in the first section of the questionnaire. The Chi-square test was used for data analysis, and P < 0.05 was statistical significance. This research showed that respondents using Positive feedback was given by respondents using both RPDs and CDs provided positive feedback, with overall high satisfaction rates. There was a statistically significant positive correlation between satisfaction levels and denture types (RPD and CD). Aesthetic aspects were the main determinant of denture satisfaction and denture users for one to five years had a stronger oral health impact profile. The satisfaction rate among RPD users was higher than that of CD users.